2008
DOI: 10.1101/lm.1188208
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin mediates a learned increase in attraction to high concentrations of benzaldehyde in aged C. elegans

Abstract: We utilized olfactory-mediated chemotaxis in Caenorhabditis elegans to examine the effect of aging on information processing and animal behavior. Wild-type (N2) young adults (day 4) initially approach and eventually avoid a point source of benzaldehyde. Aged adult animals (day 7) showed a stronger initial approach and a delayed avoidance to benzaldehyde compared with young adults. This delayed avoidance is due to an increased attraction rather than a decreased avoidance to benzaldehyde because (1) aged odr-3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Diacetyl is normally one such chemoattractant, but Morrison et al (1999) showed that worms could learn to avoid it if it was previously presented with an aversive acetic acid solution. Conversely, Torayama et al (2007) found that C. elegans became more attracted to butanone after pre-exposure to it in the presence of food, and Tsui and van der Kooy (2008) proposed that older worms displayed enhanced chemotaxis to benzaldehyde because of increased exposure to the pairing of volatile metabolites with the presence of an appetitive bacterial food source. Interestingly, increased attraction to benzaldehyde in aged worms was mediated by serotonin (Tsui and van der Kooy 2008) while butanone enhancement was not (Torayama et al 2007), suggesting that there are multiple mechanisms for sensory integration.…”
Section: Smell As the Conditioned Stimulusmentioning
confidence: 99%
See 1 more Smart Citation
“…Diacetyl is normally one such chemoattractant, but Morrison et al (1999) showed that worms could learn to avoid it if it was previously presented with an aversive acetic acid solution. Conversely, Torayama et al (2007) found that C. elegans became more attracted to butanone after pre-exposure to it in the presence of food, and Tsui and van der Kooy (2008) proposed that older worms displayed enhanced chemotaxis to benzaldehyde because of increased exposure to the pairing of volatile metabolites with the presence of an appetitive bacterial food source. Interestingly, increased attraction to benzaldehyde in aged worms was mediated by serotonin (Tsui and van der Kooy 2008) while butanone enhancement was not (Torayama et al 2007), suggesting that there are multiple mechanisms for sensory integration.…”
Section: Smell As the Conditioned Stimulusmentioning
confidence: 99%
“…Conversely, Torayama et al (2007) found that C. elegans became more attracted to butanone after pre-exposure to it in the presence of food, and Tsui and van der Kooy (2008) proposed that older worms displayed enhanced chemotaxis to benzaldehyde because of increased exposure to the pairing of volatile metabolites with the presence of an appetitive bacterial food source. Interestingly, increased attraction to benzaldehyde in aged worms was mediated by serotonin (Tsui and van der Kooy 2008) while butanone enhancement was not (Torayama et al 2007), suggesting that there are multiple mechanisms for sensory integration. Zhang et al (2005) demonstrated that worms could learn to avoid odors associated with pathogenic bacteria, preferring those associated with familiar nonpathogenic strains.…”
Section: Smell As the Conditioned Stimulusmentioning
confidence: 99%
“…4a), indicating that other Gα probably works in sensing undiluted isoamyl alcohol and driving attractive behaviour. ODR-3 is also known to mediate attraction to various odorants such as benzaldehyde and diacetyl at lower concentrations 20 , and initial attraction to but not subsequent avoidance of undiluted benzaldehyde 21 . In contrast to isoamyl alcohol, ODR-3 is not involved in avoidance of higher concentrations of benzaldehyde or diacetyl, as previously reported 14 (Fig.…”
Section: A Gα Odr-3 Mediates Bidirectional Behavioural Responsesmentioning
confidence: 99%
“…These results indicate that AWC and AWA are not involved in the response to higher concentrations of isoamyl alcohol. To determine which sensory neurons mediate avoidance of isoamyl alcohol, we examined the involvement of AWB and ADL neurons which were previously reported to be required for avoidance of repellents and higher concentrations of benzaldehyde 9,10,12,21,22 . AWB-ablated animals showed defects in avoidance of isoamyl alcohol at a higher concentration (Fig.…”
Section: A Gα Odr-3 Mediates Bidirectional Behavioural Responsesmentioning
confidence: 99%
“…elegans is controlled by serotonin signaling, making it a suitable indicator of proper serotonin signaling [501]. MICA has no affinity for serotonin receptors [502] and has no effect on serotonin sensitivity in no-Aβ controls.…”
Section: Discussionmentioning
confidence: 99%